Design and optimization of functionally graded electrodes for solid oxide fuel cells (SOFCs) by mesoscale modeling. (30th April 2022) - Yan, Zilin; He, An; Hara, Shotaro; Shikazono, Naoki
Abstract: In this study, a numerical framework for microstructure design of functionally graded (FG) electrodes of solid oxide fuel cells (SOFCs) is developed using a number of mesoscale numerical simulations. The "multi-sphere" discrete element method, kinetic Monte Carlo method and lattice Boltzmann method are used sequentially to model the powder packing, powder sintering, and electrochemical reaction in the cathode. In the current FG electrode concept, porosity gradients with linear and nonlinear profiles are considered for La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) FG-cathodes. It is shown that in a porosity graded cathode, the concentration overpotential can be mitigated by improving the gas transport. However, when the porosity of the cathode is higher than approximately 0.40, the porosity gradient design contributes little to reduce the concentration overpotential but it rather increases the activation and ohmic overpotentials. In all cases, the porosity gradient design can suppress sintering, hence the thermal stability of the cathode can be improved. For cathode with an initial thickness of 25 μm and density range of 0.40–0.65, an optimal exponential factor of P  = 1.5 is found for the best performance of the cathode. Graphical abstract: Image 1 Highlights: A numerical framework for lifetime simulation of the porosity graded cathode is developed. Realistic shapes of the particles are considered for particle packing modeling of the cathode. Influences of the microstructure on the activation, concentration and ohmic overpotentials are modeled. Optimal graded microstructure is determined from the beginning of the cathode fabrication.